GIS 3D e Pianificazione Territoriale: Prospettive di integrazione metodologica - Di Pace, Roberto; Fiduccia, Andrea (GEOmedia, 2016)
GIS 3D e Pianificazione Territoriale: Prospettive di integrazione metodologica